Online Professional Learning Networks: A Viable Solution to the Professional Development Dilemma. Issue 2 (June 2017) - Cook, Rebecca J.; Jones-Bromenshenkel, Melissa; Huisinga, Shawn; Mullins, Frank
Quality professional development must meet the demands and needs of the person engaging in the activity. However, many opportunities for special educators are often less than optimal in terms of timeliness, expertise, or applicability. This article describes the idea of online professional learning networks (PLNs) which allow for collaboration and idea sharing outside the confines of place and time. Selection criteria and tool options are described, and instructions for accessing the various options are shared. The importance of reflection regarding one's engagement in a PLN is also discussed.